2017
DOI: 10.1111/mmi.13632
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient levels of the nrdAB‐encoded ribonucleotide reductase underlie the severe growth defect of the Δhda E. coli strain

Abstract: The ATP-bound form of the Escherichia coli DnaA replication initiator protein remodels the chromosomal origin of replication, oriC, to load the replicative helicase. The primary mechanism for regulating the activity of DnaA involves the Hda and β clamp proteins, which act together to dramatically stimulate the intrinsic DNA-dependent ATPase activity of DnaA via a process termed Regulatory Inactivation of DnaA (RIDA). In addition to hyper-initiation, strains lacking hda function also exhibit cold sensitive grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…It was shown before that deletion of rrn operons affects the growth rate of cells only moderately [ 38 , 39 ]. However, in a recent study, a duplication of a similar location was observed as a suppressor of the severe growth defect of cells lacking the DnaA regulatory inactivator Hda [ 40 ]. The suppression of the slow-growth phenotype of Δhda cells was found to be the increased gene dosage for DNA polymerase I ( polA ) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown before that deletion of rrn operons affects the growth rate of cells only moderately [ 38 , 39 ]. However, in a recent study, a duplication of a similar location was observed as a suppressor of the severe growth defect of cells lacking the DnaA regulatory inactivator Hda [ 40 ]. The suppression of the slow-growth phenotype of Δhda cells was found to be the increased gene dosage for DNA polymerase I ( polA ) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent study, a duplication of a similar location was observed as a suppressor of the severe growth defect of cells lacking the DnaA regulatory inactivator Hda [ 40 ]. The suppression of the slow-growth phenotype of Δhda cells was found to be the increased gene dosage for DNA polymerase I ( polA ) [ 40 ]. This or other similar effects might be important contributors in oriX cells.…”
Section: Discussionmentioning
confidence: 99%
“…SeqA null mutants over-initiate, and because the closely spaced forks encounter unrepaired collapsed forks, growth of SeqA null cells is severely inhibited. Cells that carry too much DnaA-ATP (such as hda null cells) also over-initiate, and this is further complicated by DnaA-ATP-induced repression of nrdA B ( 61 , 62 ), resulting in lower than normal nucleotide levels. Insufficient nucleotides could slow fork movement directly, or could make it more difficult to bypass DNA lesions caused by events such as oxidative stress ( 56 , 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…These mutations affect iron/sulfur cluster synthesis, Flavin/Fe reduction, ArcA and/or respiration [ 82 , 84 ]. In the hyper-replicating cells, the gaps generated by MutM are toxic [ 10 ] and aerobic growth can be restored in the absence of MutM [ 10 ] or when PolI is overproduced [ 85 ]. Recombination repair functions are essential under these conditions [ 86 ] and the DNA damage seen in hyper-replicating cells is avoided in absence of oxygen.…”
Section: Toxic Repairmentioning
confidence: 99%